2018
DOI: 10.5539/jas.v10n9p275
|View full text |Cite
|
Sign up to set email alerts
|

Amostral Optimization of Mechanical Resistance to the Penetration of a Yellow Oxisol Under Pasture

Abstract: The degradation of pastures can be characterized by several factors, mainly due to the management adopted, so in view of the country's territorial extension and the peculiarity of each region and soil type, it is essential to develop research to improve the monitoring of the system. The objective of this study was to evaluate the effect of different sample densities to establish a mesh that gives precision in maps of spatial variability of soil mechanical resistance to root penetration to pasture areas in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…These results were similar to those obtained in simulations and lower than the sample size optimized by simulated annealing proposed by Guedes et al (2014) or the fixed sample size (50% of the initial grid) in the optimization of a sample configuration proposed by Guedes et al (2011) using a hybrid genetic algorithm and considering the efficiency of spatial prediction. In addition, these results corroborate the findings of Dias et al (2018), who evaluated the effect of sample densities and observed that a reduction in an interval of 60 to 80% of the sample grid allowed the identification of spatial variability.…”
Section: Practical Studysupporting
confidence: 88%
“…These results were similar to those obtained in simulations and lower than the sample size optimized by simulated annealing proposed by Guedes et al (2014) or the fixed sample size (50% of the initial grid) in the optimization of a sample configuration proposed by Guedes et al (2011) using a hybrid genetic algorithm and considering the efficiency of spatial prediction. In addition, these results corroborate the findings of Dias et al (2018), who evaluated the effect of sample densities and observed that a reduction in an interval of 60 to 80% of the sample grid allowed the identification of spatial variability.…”
Section: Practical Studysupporting
confidence: 88%